When lava strikes - Mann, Greyson (Mann, Greyson. Secrets of an overworld survivor, 2017)
"Will and Mina's treasure hunt turns up only terror when they start fighting over what resources to look for. But when lava strikes, can they work together to survive?"-- Provided by publisher.